Development of harvard step test an-515 based on digital integrated technology - Nuryadin, Arief; Siswantoyo, Siswantoyo (MEDIKORA, 2021)
For practitioners and academission in sports, knowing the level of physical fitness is very important. One way to measure it by using the Harvard Step Test. However, measuring physical fitness using the manual Harvard Step Test often has several drawbacks. One of them is an error in the process of calculating the pulse, which results in the final result of physical fitness measurements to be less accurate. Therefore, it is necessary to develop a valid and reliable Harvard Step Test measuring instrument based on integrated digital technology. This research uses research and development methods. The small-scale trial used 10 samples from the Regional Leadership 53 Tapak Suci Klaten Pencak silat branch, while the large scale used samples from the Bantul Anggar Branch and the Jaya Raya Sleman Badminton Board. The data analysis technique used is qualitative and quantitative analysis, while the effectiveness test used the one-tailed paired sample t-test. This research resulted in a product in the form of a Harvard Step Test based on integrated digital technology which is equipped with a manual. The trial results and effectiveness show that the Harvard Step Test, which is based on integrated digital technology, is effective to measure physical fitness in all age groups. PENGEMBANGAN HARVARD STEP TES AN-515 BERBASIS DIGITAL TEKNOLOGI TERINTEGRASI Abstrak Bagi praktisi dan akademisi di bidang olahraga, mengetahui tingkat kebugaran jasmani merupakan hal yang sangat penting. Salah satu cara mengukurnya adalah dengan menggunakan Harvard Step Test. Akan tetapi, mengukur kebugaran jasmani menggunakan Harvard Step Test manual seringkali memiliki beberapa kekurangan. Salah satunya adalah kesalahan dalam proses perhitungan denyut nadi, yang mengakibatkan hasil akhir dari pengukuran kebugaran jasmani menjadi kurang akurat. Oleh sebab itu, perlu dikembangkan alat ukur Harvard Step Test berbasis digital teknologi terintegrasi yang valid dan reliabel. Penelitian ini menggunakan metode penelitian dan pengembangan. Uji coba skala kecil menggunakan sampel dari cabang Pencak silat Pimpinan Daerah 53 Tapak Suci Klaten sebanyak 10 orang, sedangkan skala besar menggunakan sampel dari Cabang Anggar Bantul dan Pengurus Besar Bulutangkis Jaya Raya Sleman. Teknik analisis data yang digunakan adalah analisis kualitatif dan kuantitatif sedangkan pada uji efektivitas menggunakan uji one-tailed paired sample t-Test. Penelitian ini menghasilkan produk berupa Harvard Step Test berbasis digital teknologi terintegrasi yang dilengkapi buku panduan. Hasil ujicoba dan efektifitas menunjukkan bahwa Harvard Step Test yang berbasis digital teknologi terintegrasi efektif digunakan untuk mengukur kebugaran jasmani dalam semua kelompok usia.